EKSPLORASI BIBLIOMETRIK BERBASIS PEMODELAN TOPIK PADA TOP-3 JURNAL BIDANG SISTEM INFORMASI MANAJEMEN - Anne Parlina; Riri Kusumarani (Jurnal Studi Komunikasi dan Media, 2023)
A management information system (MIS) is a system that manages, processes, and presents information to management that aims to improve the quality of decisions and policies. A common misconception regarding the management information system (MIS) topic is that it mainly involves programming. This study aims to capture the intellectual structure and theme evolution of MIS by incorporating latent dirichlet allocation (LDA) into its methodology. A bibliometric analysis was conducted to evaluate the publication characteristics of the top three MIS journals (IJIM, JSIS, and MIS Quarterly: Management Information Systems) from the SCOPUS database between 1980 and 2021. Our findings indicate the trend of publishing articles, the structure of science, and the topics that stand out in the top three journals.